Isolation and Optimization of Streptokinase Production by Batch Fermentation - Patel, DR.Vipul P (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Streptokinase was isolated from β haemolytic streptococci, Streptococcus pyogenes by batch fermentation. Strain was treated with U.V radiation. Enzyme concentration was measured by Lowry’s protein estimation method. Regression analysis was performed to study the influence of different parameter like ageing period of strain, inoculum volume, corn steep liquor on the yield of enzyme. Biological activity like Fibrinolytic activity, Radial Caseinolytic activity was performed to study enzyme activity. M1 (45.04 mg/ml) batch was considered as a prominent batch as it produce almost five times higher yield than normal strain (9.68 mg/ml). Batch F6 (296.67 mg/ml) of factorial experiment was found to be most prominent for production of streptokinase enzyme as it shows almost six fold increments in production yield. Regression analysis stated that Corn steep liquor and ageing period of strain are the parameters which have positive significant effect on enzyme yield while inoculum volume has negative significant effect on yield.